Optical fiber lossy-mode resonance sensors with doped tin oxides for optical working electrode monitoring in electrochemical systems - Burnat, D.; Janczuk-Richter, M.; Niedziałkowski, P.; Białobrzeska, W.; Sezemský, Petr; Koba, M.; Straňák, Vítězslav; Bogdanowicz, R.; Ossowski, T.; Niedziółka-Jönsson, J.; Smietana, M. (SPIE, 2019)
This work discusses optical fiber sensors based on lossy-mode resonance (LMR) effect and their potential for simultaneous sensing in multiple domains, i.e., optical and electrochemical. As electrically conductive materials able to guide lossy modes, two doped tin oxides, i.e., fluorine doped tin oxide (FTO) and indium tin oxide (ITO) thin films were employed. Since the ITO-LMR sensor has already been discussed broader, this work focuses on properties of the FTO-LMR sensor and brief comparison of devices based on the two materials. In optical domain the sensitivity to surrounding medium refractive index was determined by immersing the sensors in solutions of different refractive index. Both the sensors showed sensitivity of 300 nm/RIU in a refractive index range of approx. 1.33-1.39 RIU. Electrochemical measurements were performed in 0.01 M phosphate-buffered saline (PBS, pH 7.0) to identify the influence of the applied potential on the optical response of both sensors. In applied potential from-1.0 V to 1.0 V the FTO-LMR sensor reached LMR shift of 31.3 nm compared to 23.8 nm of the ITO-LMR one. © COPYRIGHT SPIE. Downloading of the abstract is permitted for personal use only.
Keywords: Cyclic voltammetry; Electrochemistry; Fluorine-doped tin oxide (FTO); Indium tin oxide (ITO); Lossy-mode resonance (LMR); Magnetron sputtering; Optical fiber sensors; Thin films